The dangers of compressed air - Skills education Australia; Safetycare Australia Pty. Ltd. ([Australia] : Safetycare Australia)
The video program aims to increase people's awareness of the dangers of compressed air and of the importance of using compressed air tools and equipment correctly to avoid injury
Title from title screen
Keywords: Compressed air -- Physiological effect; Compressed air